From Shadows to Structures: Unveiling the Terrorism-Corruption Nexus in Developing Countries through Structural Equations Modeling (SEMs) - Riaz, Muhammad Farhan; Liaqat, Saima; Bashir, Furrukh; Boota, Mehwish (Pakistan Journal of Humanities and Social Sciences, 2024)
We utilized Confirmatory Factor Analysis (CFA) to investigate the correlational and bidirectional relationship between corruption control and terrorism control in 65 developing countries panel data from year 2000 to 2019. Significance of various parameters of observed indicators has also been empirically assessed in this research that redefine the latent variables of corruption control and terrorism control. Our empirical findings support the idea that unchecked corrupt activities sustain and spread terrorism, especially in areas where formal economic and political frameworks are weak or nonexistent. The findings clearly indicate that ineffective corruption control in developing countries lead to reduced control over terrorism. Furthermore, our study empirically shows that terrorist acts are predominantly concentrated in regions plagued by internal and external conflicts. Countries with significant military involvement in politics face a higher threat of terrorist activities. Additionally, an efficient, active, and impartial judiciary is crucial for combating corruption at all levels. The findings of this research underscore the critical need for governments in every developing country to implement economic reforms anchored in incentives to stabilize and regulate the political economy. Effectively controlling corrupt activities and terrorism offers the potential to facilitate the efficient allocation of resources and promote sustained economic growth in these nations.